Smallholder sesame farmers’ collective action to ease access to market: IPSR Innovation Profile - Kassie, Girma T.; Abate, Gashaw T.; Minot, Nicholas; Asnake, Woinishet; Worku, Y. (CGIAR System Organization, 2024)
mSmallholder sesame producers and local traders usually act individually. Therefore, they usually struggle with high transaction costs and market harassment by intermediaries and other agents along the value chain. Small groups will be formed voluntarily by participating farmers and traders to make marketing decisions more efficient.